Choccosuisee - The New "Extended Extended" Passing Off - Saunders, Katherine (Victoria University of Wellington Law Review, 2001)
This paper analyses the recent British passing off case Chocosuisse. The paper attempts to set out the historical nature of passing off and then analyse the developments in Chocosuisse in light of the historical origins of the tort. The relationship between tort and equity is discussed, with particular attention paid to the 'fusion' debate. The acceptance of an 'unclean hands' defence in Chocosuisse and its appropriateness is discussed. The author proposes alternative means of achieving similar goals that are more consistent with both passing off's origins and the relationship between tort and equity. The new Chocosuisse requirements for extended passing off goodwill are discussed. The author considers potential problems that the new requirements will create for extended passing off in and urges future courts not to follow this aspect of Chocosuisse. Finally Laddie J's use of passing off to protect correct application of geographical indicators and the inconsistency of this use with the origins of passing off are discussed. The author considers alternative means available to protect accurate application of geographical indicators.